Monteggia fracture associated with olecranon fracture-dislocation Mayo IIIB - Maljković Filip; Stanojković Aleksandar; Zekić Boris; Milanović Filip; Krivokapić Branislav (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Monteggia fractures involving olecranon fractures and dislocations present complex challenges due to the need for simultaneous stabilization of multiple joint components. These injuries require precise surgical planning and execution to restore elbow function and minimize complications such as joint instability, nonunion, and reduced mobility. Modern surgical techniques, including the use of locking plates and careful anatomical reduction, have shown to significantly improve long-term outcomes. Case outline. This case report discusses the management of a 30-year-old female patient with a Monteggia fracture and olecranon fracture-dislocation following a cycling accident. The patient underwent delayed surgery due to severe soft tissue injuries. The procedure involved ulna fixation with an olecranon plate and radial head stabilization using a FiberTapeR system (Arthrex, Naples, FL, USA). Despite incomplete rehabilitation, the patient showed satisfactory recovery with only minor limitations in elbow movement. This case emphasizes the importance of early intervention, precise reduction, and the use of modern fixation techniques in optimizing recovery for complex elbow injuries. Conclusions. Effective treatment of Monteggia fractures associated with olecranon dislocation requires early intervention, precise anatomical reduction, and the use of modern fixation techniques to ensure optimal functional outcomes and minimize long-term complications.